Carbon nanotube reinforced hybrid composites: computational modeling of environmental fatigue and usability for wind blades. - Dai, G.; Mishnaevsky Jr, L
The potential of advanced carbon/glass hybrid reinforced composites with secondary carbon nanotube reinforcement for wind energy applications is investigated here with the use of computational experiments. Fatigue behavior of hybrid as well as glass and carbon fiber reinforced composites with and without secondary CNT reinforcement is simulated using multiscale 3D unit cells. The materials behavior under both mechanical cyclic loading and combined mechanical and environmental loading (with phase properties degraded due to the moisture effects)is studied. The multiscale unit cells are generated automatically using the Python based code. 3D computational studies of environment and fatigue analyses of multiscale composites with secondary nano-scale reinforcement in different material phases and different CNTs arrangements are carried out systematically in this paper. It was demonstrated that composites with the secondary CNT reinforcements (especially, aligned tubes)present superior fatigue performances than those without reinforcements, also under combined environmental and cyclic mechanical loading. This effect is stronger for carbon composites, than for hybrid and glass composites.
Keywords: NANO COMPOSITES; CARBON NANOTUBES; FATIGUE; FINITE ELEMENT ANALYSIS (FEA)